Widely Tunable Dual-Wavelength Thulium-doped fiber laser Operating in 1.8-2.0 mm Region - Ahmad, Harith; Samion, Muhamad Zharif; Thambiratnam, Kavintheran; Yasin, Moh (Elsevier, 2019)
In this work, a tunable dual-wavelength fiber laser (DWFL) with a simple setup is proposed and demonstrated for operation in the 2.0-micron wavelength region. The proposed system employs a ring cavity with a 4-m bi-directionally pumped thulium-doped fiber (TDF) as the linear gain medium, with an inner ring cavity incorporating two tunable bandpass filters (TBPFs) used to generate the desired tunable dual-wavelength output. By fine-tuning the loss of the cavity, peaks of similar intensities for both lasing wavelengths can be obtained by overcoming suppression induced by the homogenous broadening effect, thus producing a stable dual-wavelength output. The widest channel spacing obtained is 183.6 nm, and both lasing wavelengths can be tuned across the 1.8-2.0-micron region by just adjusting the passbands of the TBPFs. The generated dual-wavelength laser has a high signal-to-noise ratio of 66 dB, and its 3-dB bandwidth is measured to be around 0.07 nm. The laser is highly stable, with little-to-none peak fluctuations and no wavelength shift in the lasing wavelengths. The proposed laser is suitable for use in multiple applications near the 2.0-micron region, such as biomedical and industrial applications due to its eye-safe properties.